2023
DOI: 10.3390/ijms241612996
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Voltage-Gating and Hysteresis of Lysenin Channels by Cu2+ Ions

Andrew Bogard,
Pangaea W. Finn,
Aviana R. Smith
et al.

Abstract: The intricate voltage regulation presented by lysenin channels reconstituted in artificial lipid membranes leads to a strong hysteresis in conductance, bistability, and memory. Prior investigations on lysenin channels indicate that the hysteresis is modulated by multivalent cations which are also capable of eliciting single-step conformational changes and transitions to stable closed or sub-conducting states. However, the influence on voltage regulation of Cu2+ ions, capable of completely closing the lysenin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…While the effect has been demonstrated in the context of channel-facilitated transport, to the best of our knowledge, it has not previously been linked to changes in channel conformations [53][54][55]. Although it was previously observed that not only the bathing electrolyte composition [19,[56][57][58] but also the electrolyte concentration [19,59,60] can influence β-barrel channel gating, in the present study, we limited ourselves to 1 M salt solutions because our goal here was to demonstrate the existence of the Hofmeister effect in the voltage-induced OmpF closure.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…While the effect has been demonstrated in the context of channel-facilitated transport, to the best of our knowledge, it has not previously been linked to changes in channel conformations [53][54][55]. Although it was previously observed that not only the bathing electrolyte composition [19,[56][57][58] but also the electrolyte concentration [19,59,60] can influence β-barrel channel gating, in the present study, we limited ourselves to 1 M salt solutions because our goal here was to demonstrate the existence of the Hofmeister effect in the voltage-induced OmpF closure.…”
Section: Resultsmentioning
confidence: 84%
“…conformations [53][54][55]. Although it was previously observed that not only the bathing electrolyte composition [19,[56][57][58] but also the electrolyte concentration [19,59,60] can influence β-barrel channel gating, in the present study, we limited ourselves to 1 M salt solutions because our goal here was to demonstrate the existence of the Hofmeister effect in the voltage-induced OmpF closure. It is well-known that the voltage-induced closing of β-barrel channels depends on the composition of lipid membranes [60][61][62][63][64][65][66][67][68].…”
Section: Resultsmentioning
confidence: 96%